2021
DOI: 10.1002/ajoc.202000714
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Allylic Cycloaddition of Vinylethylene Carbonates with 3‐Nitrochromone

Abstract: An efficient method for the enantio‐ and diastereoselective formation of furanochromanones has been developed via Pd‐catalyzed asymmetric allylic cycloaddition of vinylethylene carbonates with 3‐nitrochromone. By using a palladium complex generated in situ from [Pd2(dba)3]⋅CHCl3 and phosphoramidite L4 as a catalyst, the transformation allows to rapid access furanochromanones bearing versatile nitro‐group and multi‐stereocenters in high yields with excellent enantioselectivities and moderate diastereoselectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…The transformation with good diastereoselectivities and excellent enantioselectivities could be enabled by the simply adjustment of reaction variables, such as the solvent and reaction temperature (Scheme 19). [39] …”
Section: Benzopyran‐fused Polycyclic Acetalsmentioning
confidence: 99%
“…The transformation with good diastereoselectivities and excellent enantioselectivities could be enabled by the simply adjustment of reaction variables, such as the solvent and reaction temperature (Scheme 19). [39] …”
Section: Benzopyran‐fused Polycyclic Acetalsmentioning
confidence: 99%
“…The reaction involved the treatment of 3-nitro benzopyranones 22a with vinyl ethylene carbonates 19a under similar conditions to give the corresponding ketals 22b in good yield and enantioselectivity, albeit with poor diastereoselectivity (Scheme 22). 41…”
Section: Vinyl Ethylene Carbonatesmentioning
confidence: 99%
“…The reaction involved the treatment of 3-nitro benzopyranones 22a with vinyl ethylene carbonates 19a under similar conditions to give the corresponding ketals 22b in good yield and enantioselectivity, albeit with poor diastereoselectivity (Scheme 22). 41 Interestingly, in this context, a,b-unsaturated aldehydes (poor Michael acceptors) have also been used instead of these traditional Michael acceptors. Glorious et al have shown a cooperative catalysis relying upon the iterative Tsuji-Trost allylation cascade reaction of vinyl ethylene carbonates 19a with enals 23a towards the enantioselective synthesis of 7membered lactones 23b (Scheme 23).…”
Section: Vinyl Ethylene Carbonatesmentioning
confidence: 99%
“…Generally, the enantioselective [4 + 2] cycloaddition of 2,3-dihydrofuran and [3 + 2] cycloaddition of active chromone derivatives are direct methods to access furanobenzopyran skeletons, which have been established with limited but notable examples. The catalytic Mannich–ketalization reaction of salicylaldimines and 2,3-dihydrofuran using chiral Brønsted acid or Lewis acid catalysts has been developed as the direct and effective method to achieve chiral furanobenzodihydropyran scaffolds with good reactivity and asymmetric induction (Scheme a) . Lambert and co-workers reported an elegant chiral Brønsted acid catalysis to provide oxygenated chromanes via an inverse-electron-demand Diels–Alder reaction of readily available salicylaldehyde acetals and vinyl ethers (Scheme b) .…”
mentioning
confidence: 99%
“…Very recently, Wang and co-workers developed a SaBOX/Copper­(II)-catalyzed [3 + 2] cycloaddition of γ-chromenes with quinones to provide enantioenriched benzofurochromanes (Scheme c) . Another attractive [3 + 2] cycloaddition strategy to access such structures bearing vicinal all-carbon quaternary stereogenic centers has been explored by Zhang and co-workers through utilizing Pd-catalyzed asymmetric allylic cycloaddition of vinylethylene carbonates with 3-nitro/cyanochromone (Scheme d) . Although a variety of methods have been developed for the synthesis of functionalized furanobenzopyran derivatives, broadening the substrate scope and improving efficiency from readily available feedstocks, especially in an atom and step economic manner, remain challenging and in great demand.…”
mentioning
confidence: 99%